2019
DOI: 10.1038/s41394-019-0244-2
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Description of two fractures during the use of a powered exoskeleton

Abstract: Introduction Powered robotic exoskeletons are a promising solution to enable standing and walking in patients with spinal cord injury (SCI). Although training and walking with an exoskeleton in motor complete SCI patients is considered safe, the risks of unexpected (technical) adverse events and the risk of fractures are not fully understood. This article reports the occurrence of two different cases of bone fracture during exoskeleton usage. Furthermore, advice is given for extra safety training and instructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 9 publications
(23 reference statements)
1
24
0
Order By: Relevance
“…While this was the only occurrence of a bone fracture in RAGT found through this review, there are several reports of bone fractures in overground exoskeletons (He et al, 2017 ; van Herpen et al, 2019 ). Misalignment is frequently mentioned as the assumed cause for bone fractures in overground exoskeleton devices (He et al, 2017 ; van Herpen et al, 2019 ), but this has not been discussed as a possible cause in the case report of the tibia fracture sustained during Lokomat training (Filippo et al, 2015 ). The authors of this case report discussed low bone mineral density as a possible influencing factor but did not report any details of the relevant training session or discussed other possible reasons.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…While this was the only occurrence of a bone fracture in RAGT found through this review, there are several reports of bone fractures in overground exoskeletons (He et al, 2017 ; van Herpen et al, 2019 ). Misalignment is frequently mentioned as the assumed cause for bone fractures in overground exoskeleton devices (He et al, 2017 ; van Herpen et al, 2019 ), but this has not been discussed as a possible cause in the case report of the tibia fracture sustained during Lokomat training (Filippo et al, 2015 ). The authors of this case report discussed low bone mineral density as a possible influencing factor but did not report any details of the relevant training session or discussed other possible reasons.…”
Section: Discussionmentioning
confidence: 66%
“…To the best of our knowledge, there are no reports of bone fractures in end-effector-type devices. While this was the only occurrence of a bone fracture in RAGT found through this review, there are several reports of bone fractures in overground exoskeletons (He et al, 2017;van Herpen et al, 2019). Misalignment is frequently mentioned as the assumed cause for bone fractures in overground exoskeleton devices (He et al, 2017;van Herpen et al, 2019), but this has not been discussed as a possible cause in the case report of the tibia fracture sustained during Lokomat training (Filippo et al, 2015).…”
Section: Musculoskeletal Adverse Eventsmentioning
confidence: 83%
“… Participants were required to have a buddy who received instructions about guiding the participant during multiple skills, including donning and doffing, sit-to-stand, and walking. In addition, a device related error was simulated so that both the participant and the buddy practiced trouble shooting via a graceful collapse (see van Herpen et al for a more detailed description of the trouble shooting protocol 23 ). This protocol was added to the current study from participant 7 onward, after the occurrence of a bone fracture as described in two case reports 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies found that misalignment due to suboptimal fitting can increase the metabolic cost and discomfort of the wearer producing pain, injuries [56,57] and augment the risk of bone fractures [58,59]. Therefore, the structure of the exoskeleton has to be able to adapt to the anthropometry of the users [60].…”
Section: Design and Structurementioning
confidence: 99%